The Effectiveness of Using LCD Projectors in Increasing Interest in Learning PAI Student of SMPN 3 Lemito Pohuwato District - Darmawati Darmawati; Muliani Muliani (Universitas Muhammadiyah Enrekang, 2022)
The effectiveness of using LCD Projector media on interest in PAI learning in SMPN 3 Lemito students in Pohuwato Regency. Research on the use of LCD Projector media has been carried out by several researchers, but has a different object. This study will focus on the interest in learning PAI in students of SMPN 3 Lemito in Pohuwato Regency. The focus of this research is based on the problem of lack of interest in learning PAI in students of SMPN 3 Lemito in Pohuwato Regency. To overcome this problem, it is necessary to have a learning support media, namely LCD Projector media that can effectively increase students' interest in PAI learning. This study aims to determine the effectiveness of using LCD Projector media in increasing interest in PAI learning. The research method used in this research is descriptive qualitative method with data collection based on activity and learning effectiveness and statistics with the help of SPSS for windows version 17.00. The test was carried out on the results of the Pree-test and the results of the Post-test given that the average score of the students' Post-Test results after using the LCD Projector was 80.27 with a standard deviation of 10.423. The percentage of completeness reached 87.9% because it reached 29 students who completed. This means that the Post-Test results after using the LCD Projector media are in the complete category. so that the use of LCD Projector media is effective in increasing interest in learning PAI in students of SMPN 3 Lemito in Pohuwato Regency.